Analysis for Lightning System on PPKA Building Depok Station - sunardi, sunardi; Triwijaya, Santi; Prih Raharjo, Efendy; Reinaningtyas, Elysaa (Nusantara Publisher, 2024)
The PPKA building contains vital railway equipment components. In a high level of lightning density, external protection is required to prevent damage due to direct lightning strikes. By raising and changing the position of the spritzer diagonally to a height of 12 meters , the protection radius is 27.42 meters ; by moving one of the splitzer positions in building B and raising it to a height of 9 m, the protection radius is 26 m and 20.7 meters , the same thing is done with a height of 12 meters , the protection radius is 30.6 m and 24.5 meters ; This optimization is able to protect the entire building. Rolling method sphere (RSM) obtained a radius of 60 meters. RSM Prevectron3 S50 obtained a ∆L value of 50 meters with r ESE of 110 meters , while RSM Viking V6 obtained an ∆L value of 70 meters , with r ESE of 130 meters , with the design planning option using rolling sphere is able to protect the entire building.